PERANAN POLA PENGASUHAN ORANG TUA BERPROFESI GURU MADRASAH BERASRAMA TERHADAP PEMEROLEHAN BAHASA - Afryansyah afryansyah (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
The purpose of this study was to describe the role of parental care patterns of boarding madrasah teachers on language acquisition of children aged 3 years. To achieve this goal, a qualitative descriptive research method was used with the approach of language acquisition theory (Dardjowidjojo). The study was conducted in the teacher's residents Insan Cendekia OKI during March-April 2022 with a cakap libat technique and a simple interview to two children aged 38 months and 40 months. The data analysis technique is done by analyzing the elements of phonology, morphology, and syntax that are adjusted to the age of the two children based on the theory of Soenjono Dardjowidjojo. Based on the research that has been done, the results showed that the pattern of care carried out directly by the mother and others (caregivers) have a different impact on language acquisition for children aged 3 years. KF is nurtured by grandmother (Nanny) because his father and mother teach in boarding madrasah, Kf just has phonological skills, but not good enough in morphology syntax side. Meanwhile, Hs who was taken care of directly for 24 hours by his mother (only his father who worked) had almost perfect language skills and acquisition both from the level of phonology, morphology, and syntax.